Penggunaan Media Gambar untuk Meningkatkan Hasil Belajar IPA pada Siswa Kelas V SD Katolik 13 Santu Paulus Manado - Kaunang, Bernadette J.; Sobon, Kosmas (Lentera: Jurnal Ilmiah Kependidikan, 2020)
The purpose of this research is to describe the step of using image media to improve science learning result in thirteen Chatolict elementary school of Saint Paul, Manado City. This research uses class actions research methods are carried out in the two cycles. Each cycle consisted of four steps namely: planning, action, observation and reflection. The data sources of this research is the fifth grade students of thirteen Chatolict elementary school of Saint Paul, Manado City in academic year 2018/2019 to 25 students. The techniques of data collecting were test, interview, observation and documentation. The data analysis is used by this research is kuantitatif and kualitatif data analysis. Based on the result of the research, it can be concluded that the using of image media can improve grade V students’ Science learning achievement by in thirteen Chatolict elementary school of Saint Paul, Manado City. The results showed that: (1) teacher skill in the first cycle 87,5% with good criteria and in second cycle obtained 90,65% with very good criteria; (2) student activity in the first cycle 73,75% with the criteria was active enough and in second cycle obtained 78,13% with active criteria; (3) student learning result in the first cycle 52% and the second cycle 84%. Suggestions in this researh was that: (1) using of image media could become as a teacher’s solution to improve the quality of natural science learning. (2)the teacher of learning science subject have to study the using learning methods, models and media to give learning spirit for the students.